DEVELOPMENT OF SOCIAL AND LEGAL FOUNDATIONS FOR THE REFORM OF THE FAMILY INSTITUTION IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
This article is dedicated to the topic “Social and Legal Foundations of Reforming the Family Institute in New Uzbekistan”, analyzing initiatives aimed at reforming family relations in Uzbekistan and improving the legal and social status of families. The article discusses the main principles of strengthening the social-legal role of the family, changes in the family and society, and the renewal of legal norms in the reform of the family institute. Special attention is given to issues such as gender equality, children's rights, and ensuring mutual respect and responsibility among family members. The reforms being implemented to strengthen the family institute and resolve family disputes in New Uzbekistan serve to ensure social stability and reinforce family values in society.